Evidence of local adaptation in litter flammability of a widespread fire‐adaptive pine. (28th February 2022) - Kane, Jeffrey M.; Gallagher, Michael R.; Varner, J. Morgan; Skowronski, Nicholas S.
Abstract: Fire is a strong ecological and evolutionary driver of plant species and terrestrial ecosystem dynamics. Numerous studies have shown that plant species vary widely in their flammability and associated traits that coincide with clear strategies of persistence in fire‐prone ecosystems. Yet, intraspecific variation and phenotypic plasticity in plant flammability has received substantially less attention. Some evidence has demonstrated high plasticity in flammability among populations in species adapted to low‐frequency, high severity fire regimes which suggests the capacity of local adaptation; however, intraspecific variability of species in high‐frequency, low severity fire regimes has not been conducted. Given that frequent fire‐adaptive species tend to produce fast‐flammable litter that is associated with survival following fire, we hypothesized that these species would have highly conserved leaf traits with low variation in litter flammability. We used an existing common garden study to test our hypothesis in Pinus rigida (pitch pine) with source populations that span most of its distribution in eastern North America. We examined both phenotypic and genotypic variation as well as phenotypic plasticity (relative distance plasticity index) in P. rigida leaf traits and litter flammability among populations grown in situ (population) and the same populations grown in a common garden or provenance study (provenance). Phenotypic and genotypic variation in fuel traits and litter flammability differed among source locations. Phenotypic plasticity in litter flammability among source locations were associated with fuel trait plasticity and biogeographic factors. Populations located in warmer and drier climates with presumably more frequent historical fire regimes were associated with greater plasticity in physical litter traits and their resulting flammability. Synthesis . Our study demonstrates the utility of common garden experiments to examine intraspecific variation and phenotypic plasticity in litter flammability. Our results indicate that litter flammability in Pinus rigida has the capacity for local adaptation. We hypothesize that intraspecific variation in plant flammability provides ecologically and evolutionary relevant information and that other frequent fire‐adaptive species will similarly demonstrate local adaptation in plant flammability. Abstract : Our study demonstrates the utility of common garden experiments to examine intraspecific variation and phenotypic plasticity in litter flammability. Our results indicate that litter flammability in Pinus rigida has the capacity for local adaptation. We hypothesize that intraspecific variation in plant flammability provides ecologically and evolutionary relevant information and that other frequent fire‐adaptive species will similarly demonstrate local adaptation in plant flammability.